Study of nonalcoholic fatty liver Telangana population - Patel, Parth N.; Mohiuddin, Mohd Ifthekhar (International Journal of Advances in Medicine, 2019)
Background: Among 83 patients of both sexes aged between 25 to 65 adults had NAFLD with metabolic syndrome were studied. Methods: U.S.G. biochemical study included total cholesterol, AST, ALP, S, Albumin total Bilirubin, FBS, HbA1c and blood pressure was recorded. Results: Among 16(19.2%) had grade-I (mild steatosis) 38(45.7%) had grade-II (Moderate steatosis), 29(34.9%) had grade-III (severe steatosis), The clinical manifestation were 49(59%) had BMI 22.8 to 23.2, 34(40.9%) had BMI 23.3 to 24.2. D.M status was 33(39.7%) were pre-diabetic, 50(60.2%) were diabetic mellitus. 19(22.8%) were norma- tensive, 64(77.1%) were hypertensive, 63(75.9%) were hyperlipidemic, 23(27.7%) had IHD. 4(4.81%) had MI. Mean value of total cholesterol was 223±9.2, Triglyceride 24.8±13.3, HDL 42.3±2.5, LDL 128±13.8, AST 52.8±3.6, ALT 67.2±6.8, ALP 107±11.8, S. Albumin 3.50±0.12, Total bilirubin 0.93±0.10, FBS 13.±12.2, HB A/c 9.10±402. Conclusions: The present study of NAFLD was performed by combination of radiological and laboratory techniques, greatly reducing the requirement for invasive biopsy and reduce the morbidity and mortality.